Uveitis and Multiple Sclerosis: Potential Common Causal Mutations (2019)
Uveitis, defined as inflammation of the uveal tract of the eye, is a leading cause of blindness and visual impairment throughout the world. The etiology of uveitis is complex, and autoimmunity plays a major role in its pathogenesis. Intermediate uveitis (IU), a subtype of ocular inflammation, has been associated with systemic autoimmune disorders, specifically with multiple sclerosis (MS). This article reports a rare three-generation family with several members affected by IU (four siblings) and comorbid MS (two siblings fulfilling MS diagnostic criteria and a third sibling presenting some neurological symptoms). Based on the clinical findings, we captured and sequenced whole exomes of seven pedigree members (affected and unaffected). Using a recessive model of transmission with full penetrance, we applied genetic linkage analysis to define minimal critical regions (MCRs) in suggestive or nominal regions of linkage. In these MCRs, we defined functional (some pathogenic), novel, and rare mutations that segregated as homozygous in affected and heterozygous in unaffected family members. The genes harboring these mutations, including DGKI, TNFRSF10A, GNGT1, CPAMD8, and BAFF, which are expressed in both eye and brain tissues and/or are related to autoimmune diseases, provide new avenues to evaluate the inherited causes of these devastating autoimmune conditions. © 2019, The Author(s).